Does highway accessibility influence local tax factors? - Dörr, Luisa,Gäbler, Stefanie (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
We examine how highway accessibility influences tax policy. We exploit the stagewise expansion of the
10419/214234
Keywords: Graue Literatur; Highway; infrastructure; accessibility; tax factors; municipalities; localgovernments